Floating Exchange Rates in Africa. (IMF Working Papers; Working Paper, 1988)
The paper examines the experiences of nine African countries that have introduced floating exchange rate regimes in the 1980s. The various types of market arrangements are explored, focusing on the roles of market participants. After a review of exchange rate developments under the regimes, some related concerns with respect to urban income and employment, resource allocation, and short-term instability are analyzed. In the light of this analysis, the paper suggests some policy recommendations aimed at ensuring the success of the floating regimes.